Assessment of Self-incompatibility and the Different Modes of Pollination on Seed Set and Yield of Buckwheat (Fagopyrum esculentum M.) - B, Gagan; G, Eswarappa (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The movement pattern of Apis species of honey bees Viz., Apis cerana F., Apis florea F. and Apis mellifera L. recorded during their foraging period revealed that they visited either pin or thrum morph, vice-versa thus bringing the effective cross pollination of both the flower morphs. Among the hand cross-pollinated treatments pollen from pin morph to thrum morph and pollen from thrum morph to pin morph was compatible and resulted in 100 per cent seed set. The weight of seed varied among treatments with a maximum when thrum morph was hand cross-pollinated with pollen from pin morph. Effect of different modes of pollination on seed set and yield attributing characters of buckwheat flowers revealed that maximum flower drop was recorded in control and Tetragonula iridipennis Smith pollination as compared to plots of open pollination, A. cerana pollination and A. mellifera pollination. The weight of 1000 seeds were maximum in plots pollinated with A. cerana pollination compared to the plots pollinated by A. mellifera and T. iridipennis Smith. The flower drops and fruit set in the respective treatments proved that, the pollinating agents, especially honey bees, viz., A. cerana, A. mellifera and A. florea are very much essential for effective pollination, fertilization and maximizing seed set and yield attributing parameters.